Overview: focus on laser-based manufacturing and materials processing - Quazi, Moinuddin Mohammed; Ezazi, Mohammadamin; Arslan, A.; Bashir, M. Nasir; Ali, M. M. (IOP Publishing Ltd, 2024)
The use of lasers in manufacturing and materials processing has revolutionised the way industries approach production, enabling unprecedented efficiency and precision [1]. Over the past few decades, laser-aided manufacturing and materials processing have evolved from ordinary applications to more advanced microfabrication and additive manufacturing techniques. The focus issue includes topical review papers and original research papers covering different aspects of the issue theme 'Laser-based Manufacturing and Materials Processing'. Many of them are briefly introduced below according to the elements of synthesis of advanced materials, surface modification, additive manufacturing, machining, welding, and process monitoring. Notably, the arrival of new technologies, including ultrafast lasers, has enabled unparalleled opportunities in research and development.